Comparing Kayori, the oral tradition of the Pamona Tribe, Indonesia, with the Psalms - Juanda Juanda; Pieter G.O. Sunkudon; Yewin Tjandra (HTS Teologiese Studies/Theological Studies, 2025)
Oral traditions serve as crucial repositories of cultural and spiritual values, shaping communal identity and moral instruction. However, comparative studies between indigenous oral traditions and biblical sacred texts remain underexplored, particularly in the context of theological inculturation. This study aimed to compare Kayori, an oral tradition of the Pamona people in Indonesia, with the Psalms of the Hebrew Bible, focusing on their symbolism, structure, and social functions to assess potential avenues for contextual theological integration. The study was conducted through a comparative textual analysis, examining the poetic elements, religious significance, and community roles of both traditions within their respective cultural and theological frameworks. A descriptive qualitative approach was employed, using comparative analysis and hermeneutical interpretation. Relevant literature on Kayori and the Psalms was systematically analysed to identify parallels and distinctions in theme, form, and function. While both traditions employ natural symbolism and serve as communal expressions of spirituality, they differ in theological orientation. The Psalms reflect a monotheistic framework centred on divine worship, whereas Kayori incorporates animistic and ancestral elements. In addition, the written, structured nature of the Psalms contrasts with Kayori’s oral, fluid, and adaptive performance. The study highlights the opportunities and challenges of incorporating Kayori into Christian worship. Inculturation requires theological discernment to ensure that cultural adaptation enhances biblical faithfulness rather than leading to syncretism.